2003
DOI: 10.1073/pnas.2235465100
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity as spatial insurance in heterogeneous landscapes

Abstract: The potential consequences of biodiversity loss for ecosystem functioning and services at local scales have received considerable attention during the last decade, but little is known about how biodiversity affects ecosystem processes and stability at larger spatial scales. We propose that biodiversity provides spatial insurance for ecosystem functioning by virtue of spatial exchanges among local systems in heterogeneous landscapes. We explore this hypothesis by using a simple theoretical metacommunity model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
926
10
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 854 publications
(988 citation statements)
references
References 33 publications
45
926
10
7
Order By: Relevance
“…Diversity benefits that arise from facilitation and niche partitioning might be affected by spatial scale. For example, if increasing scale brings with it an expansion of the potential niche space, then this could enhance the benefits of the marginal species (20). Furthermore, if there is greater production or accumulation of specialist pathogens or herbivores in larger versus smaller monocultures, dragging down yields, then diversity benefits might have been greater had we considered larger experimental plots or whole fields.…”
Section: Discussionmentioning
confidence: 99%
“…Diversity benefits that arise from facilitation and niche partitioning might be affected by spatial scale. For example, if increasing scale brings with it an expansion of the potential niche space, then this could enhance the benefits of the marginal species (20). Furthermore, if there is greater production or accumulation of specialist pathogens or herbivores in larger versus smaller monocultures, dragging down yields, then diversity benefits might have been greater had we considered larger experimental plots or whole fields.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, empirical studies have shown the potential for spatial coupling across food webs based on an animal's adaptive foraging behaviour [53]. The movement of predators between patches of resources can be a critical component in determining landscape-scale persistence of taxa and landscape-scale maintenance of ecosystem functions [54].…”
Section: Linking Individuals To Food Webs To Ecosystem Functionmentioning
confidence: 99%
“…One obvious candidate is spatial heterogeneity. Although only a few studies have explicitly addressed the effect spatial complexity has on stability shifts in ecosystems (Sternberg 2001;Rietkerk et al 2002;Foley et al 2003;Scheffer and Carpenter 2003), an overall smoothing effect of spatial heterogeneity seems obvious (Loreau et al 2003). Nonetheless, model analyses indicate that spatial exchange of organisms and substances tends to make even extensive spatially complex systems respond in synchrony with occasional catastrophic transitions.…”
Section: Implications For Global Changementioning
confidence: 99%